Pride of the Marines [videorecording (DVD)] - Daves, Delmer, 1904-1977; Garfield, John; Parker, Eleanor, 1922-2013; Clark, Dane, 1912-1998; Butterfield, Roger, 1907-1981 (Turner Entertainment Co. and Warner Bros. Entertainment Inc. : Distributed by Warner Home Video, 2010)
Based on the true story of a Marine blinded in the Battle of Guadalcanal during World War II. The story deals with the anger and fear he must confront once he returns home to civilian life and a world of darkness.